The Misapplication of “Mastermind”: A Mutant Species of Work for Hire and the Mystery of Disappearing Copyrights - Dougherty, Jay (The Columbia Journal of Law & the Arts, 2016)
The title of my talk is “The Misapplication of ‘Mastermind’: A Mutant Species of Work for Hire and the Mystery of Disappearing Copyrights.” Basically, we’re talking about tools for managing complex multi-author works, and the tool that seems to be developing lately in terms of motion pictures, which is a type of complex work, is what the Ninth Circuit tends to call the “mastermind” approach1 and in the Second Circuit they call the “dominant author.” 2 I think they’re roughly interchangeable ideas, and I think that the concept is being misused and isn’t necessary. I’m a very experienced motion picture production lawyer and I don’t buy the “Swiss cheese of copyright” argument that Google likes to make and the courts have endorsed, and we’ll get into that a little more as we go along.3